Quiet quitting in nursing and surgical nursing - Tsolaki, Fani (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2025)
Quiet quitting is a common phenomenon among overburdened nursing personnel. Stress, responsibility, lack of motivation, and low payment may contribute to this condition. Early detection, psychological support, training, and payment motivation may solve the problem aiming at the psychological health of nurses and the best possible care for patients.